Этико-философский смысл ‘обиды’ в произведениях Достоевского и ее значение в судьбах героев романа «Идиот» - АШИМБАЕВА, НАТАЛЬЯ ТУЙМЕБАЕВНА (SlavVaria, 2021)
The ethical and philosophical meaning of “grievance” in the works of Dostoevsky and its significance in the fate of the characters of the novel “The Idiot”. The article is devoted to the analysis, based on the material of the novel “The Idiot”, of the role of grievance in the formation of actions, behavior and the fate of Dostoevsky's characters. Grievance as a destructive factor. Grievance as a disease of human nature. Grievance and the philosophy of despair in the image of Ippolit Terentyev. Ways of love and forgiveness. From psychology to “realism in the highest sense”.